Induced seismicity associated with geothermal fluids re-injection: Poroelastic stressing, thermoelastic stressing, or transient cooling-induced permeability enhancement?. (June 2022) - Cao, Wenzhuo; Durucan, Sevket; Shi, Ji-Quan; Cai, Wu; Korre, Anna; Ratouis, Thomas
Highlights: Fluid injection and transient cooling-induced permeability enhancement is proposed as a novel mechanism for induced seismicity. Seismicity at Hellisheiði is under combined effects of pore pressure, poroelastic stress, thermal stress and permeability enhancement. Temperature dependence of induced seismicity at Hellisheiði is explained by both permeability enhancement and thermoelastic effect. Abstract: Both field injectivity and induced seismicity were reported to be inversely correlated with the temperature of re-injected fluids at the Hellisheiði geothermal field in Iceland. This observation has led to a hypothesis that transient cooling-induced permeability enhancement is a novel mechanism for induced seismicity, in addition to elevated fluid pressure, poroelastic stressing, and thermoelastic stressing in geothermal environments. In this work, a 3D calibrated coupled THM model was developed to model the colder fluids re-injection process over a 1-year period and evaluate the potential for induced seismicity in terms of Coulomb stress changes at the Hellisheiði geothermal field. Three modelling scenarios taking into account respectively the poroelastic effect, thermoporoelastic effect, and thermoporoelastic effect with permeability enhancement, were examined and compared to identify the dominant mechanism for the recorded seismicity and examine the contribution from each individual mechanism. Results have shown that, under normal fluid re-injection pressure and temperature conditions, the permeability enhancement effect is the dominant mechanism for induced seismicity at the Hellisheiði geothermal field. Specifically, the contribution to Coulomb stress changes from the permeability enhancement effect is almost twice of that from the thermoelastic stressing, which is in turn two orders of magnitude larger than that from the poroelastic stressing. It has also been noted that, when reducing temperature of re-injected fluids from 120°C to 20°C, the temperature change is increased by 2.1 times at 1, 000 m depth, while the amount of mass flow by around 4 times. Thus, the amount of heat transferred can be increased 8.4 times by lowering temperature of the injected fluids, which explains the high sensitivity of induced seismicity to temperature. Outcomes of this work suggest temperature control of injected fluids as a feasible regulation method to mitigate against injection-induced seismic risk in geothermal reservoirs.